REPRESENTATION OF GENDER ROLES IN THE BBC DRAMA TELEVISION SERIES “PEAKY BLINDERS” - Triputri HS, Dian Rezky; Iskandar, Iskandar; Halim, Abd (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
AbstractThis study aims to examine the representation of male and female characters in a feminine or masculine way in the BBC drama television series “Peaky Blinders” and the researcher wants to look inti how gender role construction effect male and female’s characters as reflected in “Peaky Blinders” series. The qualitative descriptive method is the method used in this study. The data in this study were taken from the transcript and observed the behavior of the character based on their gender in the Peaky Blinders series. The result of this study is most of the man characters of this series are adopted conventional gender role while women portrayed as typically challenge some of the conventional gender roles but also conform many negative female stereotypes. In addition, the results of the study also found the effect of gender roles on Peaky Blinders, namely economic pressure, psychological pressure and dependency on decision making.Keywords: Gender Roles, Representation, Social Role, Tv Series and media, Peaky Blinders